Latch Applicator for Efficient Delivery of Dissolving Microneedles Based on Rapid Release of Elastic Strain Energy by Thumb Force (Adv. Funct. Mater. 11/2023). (10th March 2023) - Kang, Geonwoo; Kim, Minkyung; Yang, Huisuk; Shin, Jiwoo; Sim, Jeeho; Ahn, Hyeri; Jang, Mingyu; Kim, Youseong; Min, Hye Su; Jung, Hyungil
Abstract : Latch Applicator In article number 2210805, Hyungil Jung and co‐workers develop a novel applicator that enables efficient skin insertion of dissolving microneedle patches with optimized force and velocity. It is cost‐competitive with simple components and easy to use with the thumb‐force operation. Using a model antigen, they show that the microneedle and applicator system can produce significantly higher antibodies than intramuscular injection.